Water & wastewater infrastructure : energy efficiency and sustainability - Spellman, Frank R. (CRC Press, Taylor & Francis, 2013)
"Water and wastewater facilities use large amounts of energy in the form of electricity. One way of keeping energy costs under control is by using renewable or alternative energy supplies. This book discusses the best management practices, innovations, cost-cutting measures, and energy efficiency procedures needed to maintain top-notch functional operation. With energy use now the highest operational cost factor in water plants, the text pays considerable attention to replacing conventional energy supplies with renewable energy sources, discussing these sources and their possible application in detail"--